Case Report: Stretching the limits—late valvuloplasty for THV dysfunction following redo mitral valve-in-valve implantation - Meier, David; Tzimas, Georgios; Akodad, Mariama; Husain, Ali; Dundas, James; Jelisejevas, Julius; Cheung, Anson; Sellers, Stephanie L.; Leipsic, Jonathon A.; Blanke, Philipp; Wood, David A.; Sathananthan, Janarthanan; et al. (Frontiers in Cardiovascular Medicine, 2023)
Late balloon valvuloplasty can be used to treat under-expansion-related transcatheter heart valve (THV) dysfunction. Whether this can be performed following redo THV implantation is unknown. Herein we report a case of a 72-year-old mal presenting with symptomatic gradient elevation following redo mitral valve-in-valve implantation. The patients was successfully treated with late balloon valvuloplasty with gradient improvement. In conclusion, late valvuloplasty appears effective even with several layers of valves. However, larger studies are requires to further clarify the role of this approach.